On Some Fractional Stochastic Integrodifferential Equations in Hilbert Space - Hamdy M. Ahmed (International Journal of Mathematics and Mathematical Sciences, 2009)
We study a class of fractional stochastic integrodifferential equations considered in a real Hilbert space. The existence and uniqueness of the Mild solutions of the considered problem is also studied. We also give an application for stochastic integropartial differential equations of fractional order.